The Determinants of Trade Credit in the U.S. Total Manufacturing Sector - Nadiri, M. I. (Econometrica, 1969)
This paper estimates a model specifying the determinants of trade credit in the United States total manufacturing sector for the postwar period. Trade credit is considered as a selling expense, like advertising outlays. Its determinants are derived from a profit maximization model in which the price, volume of output, and the selling costs are all variables to be jointly determined. The opportunity or cost of accounts receivable and accounts payable are specified and the response of these accounts as well as net trade credit to changes in various monetary decision variables is examined. TRADE CREDIT HAS been a major and growing source of finance in all sectors of the United States economy since World War II. Its volume and widespread use have not been matched by any other kind of business financing. Yet trade credit, like other components of working capital, has received little attention in the literature. One reason for this neglect is that trade credit is buried in the distribution activity of the firm, and sorting out the complex institutional factors that influence its behavior is extremely difficult. The few available studies on the subject have been concerned primarily with assessing the response of trade credit to changes in monetary policy. Rarely has attention been given to developing an optimal model of trade credit based on the theory of the firm, to specifying the opportunity cost of extending or receiving trade credit, or to incorporating the influence of changes in the monetary policy instruments on the optimal level of trade credit. In this paper we attempt to analyze these three problems. The brief discussion in Section 2 introduces the issues. The theoretical framework for the study is sketched in Section 3. In Section 3a, the concept of opportunity or user costs of accounts receivable and payable is developed. The relationship and response of these forms of trade credit to changes in monetary policy are discussed in Section 3b. The adjustment process is formulated in Section 3c. The empirical results of the model for accounts receivable, accounts payable, and net trade credit, i.e., the difference between accounts receivable and payable, are presented and analyzed in Section 4. The paper is concluded with a summary and an appendix describing the data sources and definitions of the variables used in the study.